Costs of vaginal delivery and Caesarean section at a tertiary level public hospital in Islamabad, Pakistan - Zaman Shakila; Khan Attia (BMC, 2010)
Abstract Background Public hospitals in developing countries, rather than the preventive and primary healthcare sectors, are the major consumers of healthcare resources. Imbalances in rational, equitable and efficient allocation of scarce resources lie in the scarcity of research & information on economic aspects of health care. The objective of this study was to determine the average cost of a spontaneous vaginal delivery and Caesarean section in a tertiary level government hospital in Islamabad, Pakistan and to estimate the out of pocket expenditures to households using these services. Methods This hospital based cost accounting cross sectional study determines the average cost of vaginal delivery and Caesarean section from two perspectives, the patient's and the hospital. From the patient's perspective direct and indirect expenditures of 133 post-partum mothers (65 delivered by Caesarean section & 68 by spontaneous vaginal delivery) admitted in the maternity general ward were determined. From the hospital perspective the step down methodology was adopted, capital and recurrent costs were determined from inputs and cost centers. Results The average cost for a spontaneous vaginal delivery from the hospital's side was 40 US$ (2688 rupees) and from the patient's perspective was 79 US$ (5278 rupees). The average cost for a Caesarean section from the hospital side was 162 US$ (10868 rupees) and 204 US$ (13678 rupees) from the patient's side. Average monthly household income was 141 ± 87 US$ for spontaneous vaginal delivery and 168 ± 97 US$ for Caesarean section. Three fourth (74%) of households had a monthly income of less than 149 US$ (10000 rupees). Conclusion The apparently "free" maternity care at government hospitals involves substantial hidden and unpredicted costs. The anticipated fear of these unpredicted costs may be major factor for many poor households to seek cheaper alternate maternity healthcare.